RETRACTED ARTICLE: TRG-AS1 is a potent driver of oncogenicity of tongue squamous cell carcinoma through microRNA-543/Yes-associated protein 1 axis regulation. Issue 15 (2nd August 2020) - He, Shuwei; Wang, Xu; Zhang, Jingjing; Zhou, Fan; Li, Lei; Han, Xingmin
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Shuwei He, Xu Wang, Jingjing Zhang, Fan Zhou, Lei Li, and Xingmin Han. TRG-AS1 is a potent driver of oncogenicity of tongue squamous cell carcinoma through microRNA-543/Yes-associated protein 1 axis regulation. Cell Cycle. 2020;19(15):1969-1982. doi:10.1080/15384101.2020.1786622. Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors checked their data and confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. The authors apologise for this oversight. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.